Developing English Course Syllabus And Course Material By Integrating The Life Story Of Sam Ratulangi - Hasan Basri, Muhammad; Anggraini Sebayang, F. Ari; C. Ranuntu, Garryn (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The study aims to develop English subject syllabus and course material by integrating the life story of Sam Ratulangi in Sam Ratulangi University. The researchers employ need analysis as the core of this research. Besides, this study also provides questionnaire for students signing in Bahasa Inggris course as well as the graduates of the subject. Interview is conducted to English lecturers and alumni of Sam Ratulangi University. To support the data mentioned, document analysis is administered to investigate the current syllabus along with textbook as course material of Bahasa Inggris course. The population of this research is the first-year students of Sam Ratulangi University from four departments (department of English literature and Indonesia literature representing social studies while department of pharmacy and nursing representing science studies). This study applies Slovin method in selecting the sampling. Descriptive research is applied in this study. It also employs both quantitative and qualitative method. Responses to questionnaire is qualitatively analyzed using The Likert Scale. Instead of using five rating scale, this study addresses only a four-point rating system since it focuses mostly on making decisions based on the needs of the students. The data from interview, document analysis, and test is analyzed quantitatively. The result and product of this research is the proper syllabus along with the course materials based on the students’ needs. Moreover, it promotes the systematic procedure in designing and developing a course both from syllabus aspect and course material.